A Reversible Cause of Skin Hyperpigmentation and Postural Hypotension. (10th June 2013) - Cherqaoui, Rabia; Husain, Mehreen; Madduri, Sujay; Okolie, Pamela; Nunlee-Bland, Gail; Williams, James
Abstract : Vitamin B12 deficiency results in neuropsychiatric, hematologic, gynecologic, cardiovascular, and cutaneous manifestations. It is seen most commonly in the elderly, malabsorption diseases (>60% of all cases), vegans, and vegetarians. Manifestations of pernicious anemia may be similar to Addison disease and may lead to a misdiagnosis. Herein, we report two cases of vitamin B12 deficiency in which clinical features shared many similarities with Addison disease. Both patients presented with progressive darkening of hands and postural hypotension that reversed with replenishment of vitamin B12 . Vitamin B12 deficiency should be considered in patients presenting with skin lesions especially with other coexisting autoimmune diseases.